Improving freshwater ecosystem assessment via the integration of eDNA-based multitrophic biotic groups - Minglei Ren; Xue Gong; Mengdie Geng; Ting Hu; Ang Hu; Li Chen; Guangjie Chen; Jianjun Wang (Water Research, 2026)

Unveiling forest vertical structure across China through stratified effective plant area index using extensive UAV LiDAR and multi-source remote sensing data - Zhiyong Qi; Zitong Bai; Haitao Yang; Yao Wang; Kai Cheng; Zekun Yang; Ang Chen; Tianyu Xiang; Yu Ren; Yixuan Zhang; Yuling Chen; Qingpeng Wang; et al. (Remote Sensing of Environment, 2026)

Hypoxia-induced downregulation of cAMP drives Ganoderic acid biosynthesis and restricts biofilm development in Ganoderma lucidum - Siyi Wang; Li Tian; Faqin Li; Qin Wang; Yanan Tan; Yanda Ning; Xuewei Cao; Yueqian Liu; Jiaolei Shangguan; Huihui Li; Ailiang Jiang; Mingwen Zhao; et al. (Food Research International, 2026)

Layer-explicit forest understory measurement: Assessing the capability of UAV LiDAR to extract understory vegetation structure - Zhiyong Qi; Haitao Yang; Zekun Yang; Zitong Bai; Ang Chen; Yixuan Zhang; Yu Ren; Junmin Zhang; Tianyu Xiang; Shiyu Yan; Guangcai Xu; Qinghua Guo (Agricultural and Forest Meteorology, 2026)

Organophosphate triesters and diesters in the Yellow River Basin (Shandong section): Geographical patterns, land use correlates and compound-specific source apportionment - Yuting Ren; Lin Zhu; Huijie Dang; Lili Cui; Ang Zhao; Chao Wei; Mei Wang (Marine Pollution Bulletin, 2026)

Surface-engineered Mn–Prussian Blue analogue with dual redox centers for high-performance hybrid capacitive deionization - Jianeng Ji; Jun Yang; Zhiqiang Wu; He Ren; Hao Fu; Chunyan Li; Minjie Shi; Edison Huixiang Ang (Chemical Engineering Journal, 2026)

Depth Stratification Shapes Viral Diversity, Interactions, and Metabolic Potential in a Deep Freshwater Lake - Zong Li; Minglei Ren; Ang Hu; Fanfan Meng; Jianjun Wang (Molecular Ecology, 2026)
Deep freshwater lakes exhibit distinct microbial community stratification across depth gradients, which plays important roles in biogeochemical cycling and ecosystem stability. As crucial regulators of microbiome composition and function, viruses may play key ecological roles in these stratified systems, yet their distribution patterns and ecological significance in deep‐lake surface sediments remain poorly understood. Here, we assessed viral community dynamics and functional potential across the entire water depth gradient (0–155 m) of Fuxian Lake using metagenomics from 44 surface sediment samples. A total of 11,523 viral OTUs were recovered, with only 18% annotated to the family level and approximately 93% classified as putatively lytic. Viral communities showed systematic depth‐related shifts across multiple dimensions. Specifically, alpha diversity, community turnover, and stochastic assembly processes increased significantly with water depth, accompanied by enhanced lytic virus dominance and larger genome sizes. Predicted virus‐host association networks transitioned from highly connected and generalized at shallow depths to increasingly sparse and specialized at greater depths. Virus‐encoded auxiliary metabolic genes showed significantly increasing abundance with water depth, along with functional shifts from host defense to enhanced biosynthesis and energy metabolism, especially regarding carbon fixation and organic matter degradation. Collectively, these results highlight the importance of water depth gradients in structuring viral communities within surface sediments and expand our understanding of viral ecological functions in deep lake ecosystems.

Mechanisms of 1-methylcyclopropene (1-MCP) in regulating ethylene signal transduction and its role in stress responses: A review - ShiMing Guo; KaiYi Xue; ShaoYan Si; JianWen Gu; Li Liu; WeiLan Yan; Ang Zhang; PengFei Ren; Xin Du (Plant Science, 2026)

Active control of autoignition inside prechamber for turbulent jet ignition regulation: An optical investigation - Jinze Li; Zhuohang Li; Yezeng Fan; Tiankui Zhu; Zhan Gao; Fei Ren; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Validating recent global canopy height maps over China's forests based on UAV lidar data - Ang Chen; Kai Cheng; Yuling Chen; Zhiyong Qi; Haitao Yang; Yu Ren; Zekun Yang; Mengxi Chen; Jiachen Xu; Yixuan Zhang; Guoran Huang; Tianyu Xiang; et al. (Remote Sensing of Environment, 2025)

Development and characterization of magnetic cellulose adsorbents functionalized with polyacrylic acid - Chengmin Hou; Zi'’ang Zhao; Fanglin Li; Yuan Bai; Chuangchuang Ren; Chenyu Li; Ze Fan; Wanting Jia; Ying Zhang; Weimin Yan; Yuru Li; Yiting Yang; et al. (Journal of Water Process Engineering, 2025)

Temporal dynamics of gonadal development and reproduction of wild Manila clam (Ruditapes philippinarum) in the Xiaoqing River estuary, Laizhou Bay - Lulei Liu; Suyan Xue; Ang Li; Yushui Ren; Ling Zhu; Jiaqi Li; Longzhen Liu; Yuze Tang; Yanguo Qiu; Yuze Mao (Estuarine, Coastal and Shelf Science, 2025)

Intestinal microbiota responses to environmental microbiomes and factors across populations of the Manila clam Ruditapes philippinarum - Longzhen Liu; Lulei Liu; Haonan Zhuang; Ang Li; Zirong Liu; Minghui Jiao; Jiamin Li; Suyan Xue; Jiaqi Li; Yushui Ren; Yuze Mao (Marine Environmental Research, 2025)

Holocene coral assemblages reveal similarities to living communities in Singapore's urban reef environment - Y.K. Samuel Chan; Ambert C.F. Ang; Min Choo; Ren Min Oh; Kyle M. Morgan; Peter A. Todd; Michael J. O'Leary; Danwei Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Experimental study of thermal comfort by variable temperature and velocity air supply system in operating room - Bin Zhou; Ang Wang; Hui Ren; Jie Xia; Fan Peng; Shao-Cong Wang; Yi-Chu Wang; Hao-Yi Zhao; Wen-Jie Li; Mei-Lan Tan; Risto Kosonen (Building and Environment, 2025)

MAX-DOAS observations of pollutant distribution and transboundary transport in typical regions of China - Hongmei Ren; Ang Li; Zhaokun Hu; Hairong Zhang; Jiangman Xu; Xinyan Yang; Jinji Ma; Shuai Wang (Journal of Environmental Sciences, 2025)

Field questionnaire survey on thermal comfort of medical personnel in operating rooms for hospitals in Nanjing - Ang Wang; Shao-Cong Wang; Fan Peng; Jie Xia; Hui Ren; Mei-Lan Tan; Bin Zhou (Energy and Buildings, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Mechanism of improved cellulase production by Trichoderma reesei in water-supply solid-state fermentation - Wenjing Xue; Yiru Sheng; Yukai Tai; Juan Ding; Ran He; Yale Jiang; Bangchao Zhong; Jian He; Ang Ren; Qin He (Bioresource Technology, 2025)

Trait–environmental relationships reveal microbial strategies of environmental adaptation - Minglei Ren; Ang Hu; Zhonghua Zhao; Xiaolong Yao; Ismael Aaron Kimirei; Lu Zhang; Jianjun Wang (Ecology, 2025)
Microbial trait variation along environmental gradients is crucial to understanding their ecological adaptation mechanisms. With the increasing availability of microbial genomes, making full use of the genome‐based traits to decipher their adaptation strategies becomes promising and urgent. Here, we examined microbial communities in water and sediments of 20 East African lakes with pH values ranging from 7.2 to 10.1 through taxonomic profiling and genome‐centric metagenomics. We identified functional traits important for microbial adaptation to the stresses of alkalinity and salinity based on the significant trait–environment relationships (TERs), including those involved in cytoplasmic pH homeostasis, compatible solute accumulation, cell envelope modification, and energy requisition. By integrating these significant traits, we further developed an environmental adaptation index to quantify the species‐level adaptive capacity for environmental stresses, such as high pH environments. The adaptation index of pH showed consistently significant positive relationships with species pH optima across regional and global genomic datasets from freshwater, marine, and soda lake ecosystems. The generality of the index for quantifying environmental adaptation was demonstrated by showing significant relationships with the species niche optima for the gradients of soil temperature and seawater salinity. These results highlight the importance of TERs in facilitating the inference of microbial genomic‐based adaptation mechanisms and expand our understanding of ecological adaptive strategies along environmental gradients.

Analysis of the softening-melting mechanism of cold-bonded briquette from return sinter fines - Ying Li; Dejin Qiu; Manqing Li; Yuandong Xiong; Timo Fabritius; Su Cao; Ang Li; Abdallah Ahmed Elsherbiny; Jie Ren; Han Wei; Yaowei Yu (Journal of Cleaner Production, 2025)

Stratified charge assisted jet ignition mode (SCAJI) for low-speed two-stroke Otto cycle ammonia marine engine - Zhuohang Li; Yezeng Fan; Jinze Li; Kaijian Wu; Zhenyingnan Zhang; Fei Ren; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Acidic proteomes are linked to microbial alkaline preference in African lakes - Minglei Ren; Ang Hu; Lu Zhang; Xiaolong Yao; Zhonghua Zhao; Ismael Aaron Kimirei; Jianjun Wang (Water Research, 2024)

Marine microplastics enhance release of arsenic in coastal aquifer during seawater intrusion process - Chengpeng Yuan; Liyang Hu; Zhefan Ren; Xiaoyun Xu; Xiangyang Gui; Xuan-ang Gong; Rui Wu; Jingke Sima; Xinde Cao (Journal of Hazardous Materials, 2024)

Sustainable reprocessing of lithium iron phosphate batteries: A recovery approach using liquid-phase method at reduced temperature - Tingyan Ren; Bolin Zou; Bin Cai; Tong Liang; Junhao Chen; Rui Huang; Dahai Yang; Hongfa Xiang; Edison Huixiang Ang; Xiaohui Song (Waste Management, 2024)

McPrA - A new gas profile inversion algorithm for MAX-DOAS and apply to 50 m vertical resolution - Jiangyi Zheng; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Bo Ren; Feng Hu; Zhaokun Hu; Yinsheng Lv; Zhidong Zhang; Wenqing Liu (Science of The Total Environment, 2023)

Observation on the aerosol and ozone precursors in suburban areas of Shenzhen and analysis of potential source based on MAX-DOAS - Hairong Zhang; Ang Li; Zhaokun Hu; Hongmei Ren; Hongyan Zhong; Jianfeng Guo; Long Yun; Mingdi Zhang (Journal of Environmental Sciences, 2023)

Insight of soot nanostructure and oxidation behavior in ammonia / ethylene coaxial diffusion flame - Luoxi Wang; Fei Ren; Xiaogang Cheng; Zhan Gao; Ang Li; Lei Zhu; Zhen Huang (Fuel, 2023)

Evaluation and measurement of tropospheric glyoxal retrieved from MAX-DOAS in Shenzhen, China - Hairong Zhang; Ang Li; Zhaokun Hu; Jianfeng Guo; Long Yun; Mingdi Zhang; Hongmei Ren; Hongyan Zhong; Jiangman Xu (Science of The Total Environment, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Comparison of alive and dead benthic foraminiferal fauna off the Changjiang Estuary: Understanding water-mass properties and taphonomic processes - Feng Jiang; Daidu Fan; Quanhong Zhao; Yijing Wu; Fahui Ren; Yan Liu; Ang Li (Frontiers in Marine Science, 2023)
Benthic foraminifera (BF) are utilized in palaeo-environmental reconstruction based on our understanding of how living individuals respond to environmental variations. However, there is still a lack of empirical insight into how non-environmental factors, such as taphonomic processes, influence the preservations of fossil BF in strata. In this study, we compare the spatial distribution and composition of alive and dead BF fauna in surface sediments to elucidate how well fossil foraminiferal fauna mirror quasi-contemporary alive BF groups indicative of different water masses off a mega-river (Changjiang) estuary, which is characterized by intense and complex river-sea interactions. On-site measurements of bottom water salinity, temperature, and dissolved oxygen were conducted in the summer to determine water mass properties. A same-site comparison of alive (Rose Bengal stained) and dead foraminiferal fauna in surface sediment samples over 73 stations was then carried out. Q-mode Hierarchical clustering analysis was used to differentiate foraminiferal assemblages based on the relative abundance of common species. Three distinct regions with different water-mass properties were identified. The distribution pattern of dead foraminiferal fauna is mainly inherited from alive fauna, while the density and diversity of the dead fauna were found to be higher than those of the alive one. Both alive and dead fauna were clustered into four assemblages. A few common alive species (small-agglutinated and thin-calcareous) were rarely found in dead fauna, and a few common dead species (preferring low temperature and indicating allochthonous sources) were rarely present in alive fauna. The alive foraminiferal abundance and diversity were mainly determined by food resources and environmental properties of salinity and temperature. Alive foraminiferal assemblages were separated by different water masses determined by river-sea interactions off the Changjiang Estuary. The “time-averaging” effect was found to be responsible for the higher density and diversity of the dead fauna. Disintegration of agglutinated tests, dissolution of calcareous tests and selective transportation were observed to contribute to the different species compositions between the alive and dead fauna. Nevertheless, indicative species-environment relations in alive and taphocoenose fauna were found to be almost homologous among most common species. This suggests that distinct benthic foraminiferal assemblages can be used to effectively differentiate between different water masses in the study coastal seas.

Intrinsic ionic confinement dynamic engineering of ionomers with low dielectric-k, high healing and stretchability for electronic device reconfiguration - Jingwen Wang; Yapeng Zheng; Wei Ren; Edison Huixiang Ang; Lei Song; Jixin Zhu; Yuan Hu (Chemical Engineering Journal, 2023)

Phospholipase D and phosphatidic acid mediate regulation in the biosynthesis of spermidine and ganoderic acids by activating GlMyb in Ganoderma lucidum under heat stress - Xiaofei Han; Zi Wang; Lingyan Shi; Jing Zhu; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2022)
Polyamines are essential for all kinds of organisms and take part in the regulation of multiple biological processes. Our previous study revealed that heat stress promoted the conversion of putrescine to spermidine and subsequently promoted the accumulation of ganoderic acids (GAs). However, how heat stress affects polyamine homeostasis remains unclear. To explore the underlying mechanism by which heat stress promoted spermidine biosynthesis, we assessed the effects of signalling molecules that respond to heat stress on spermidine biosynthesis. Our data suggested that heat stress‐induced spermidine biosynthesis and GAs accumulation via a phospholipase D (PLD)‐mediated phosphatidic acid (PA) signal. Further research revealed that the transcription factor GlMyb promoted spermidine biosynthesis via regulating spermidine synthase genes ( spds1 and spds2 ) expression by directly bonding to their promoters and it responded to heat stress and PA signal. In summary, heat stress activated GlMyb by PLD‐mediated PA signalling and subsequently induced the expression of spds1 and spds2 to promote the biosynthesis of spermidine and the accumulation of GAs. Our findings firstly reveal a detailed mechanism by which heat signalling regulates polyamine homeostasis by PLD‐mediated PA signal in fungi and provide a greater understanding of how organisms alter polyamine levels in response to environmental changes.

Polycyclic aromatic hydrocarbons (PAHs) in the upstream rivers of Taihu Lake Basin, China: spatial distribution, sources and environmental risk - Lingling Wang; Xiaoming Ren; Xiaoping Wang; Perran Ye; Fei Wang; Jiade Cheng; Yan Chen; Ang Yu; Limin Zhang; Yang Qiu (Environmental Science and Pollution Research, 2022)

Microbial diversity of sub-bottom sediment cores from a tropical reef system - Ren Min Oh; Zheng Bin Randolph Quek; Yong Kit Samuel Chan; Ambert Chiam Foong Ang; Michael J. O’Leary; Danwei Huang; Benjamin J. Wainwright (Coral Reefs, 2022)

Improvement of laccase activity by silencing PacC in Ganoderma lucidum - Jing Zhu; Shuqi Song; Lindan Lian; Liang Shi; Ang Ren; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2022)

Recent improvements to the physical model of the Bohai Sea, the Yellow Sea and the East China Sea Operational Oceanography Forecasting System - Ang Li; Xueming Zhu; Yunfei Zhang; Shihe Ren; Miaoyin Zhang; Ziqing Zu; Hui Wang (Acta Oceanologica Sinica, 2021)

Swi6B , an alternative splicing isoform of Swi6, mediates the cell wall integrity of Ganoderma lucidum - Lingdan Lian; Guang Zhang; Jing Zhu; Yunxiao Wang; Lingshuai Wang; Rui Liu; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary The cell wall integrity (CWI) signaling activates the transcription factor Swi6 through a MAPK signaling cascade in response to cell wall stresses. In this study, we observed two different mRNA variants of swi6 ( GlSwi6A and GlSwi6B ) existed, due to alternative splicing. Besides, the expression level of GlSwi6B was higher than that of the GlSwi6A mRNA variant. The co‐silencing of GlSwi6A and GlSwi6B was more sensitive to cell wall stress compared with WT, resulting in a decrease of 78% and 76% in chitin and β‐1,3‐ d ‐glucan content respectively. However, only the overexpression of GlSwi6B decreased the sensitivity to cell wall stress and increased the content of chitin and β‐1,3‐ d ‐glucan compared with the WT strain. Furthermore, Y1H, EMSA and BLI assays revealed that the GlSwi6B could bind to the promoters of chitin and glucan synthesis genes (GL24454 and GL18134). However, the binding phenome has not been observed in the isoform GlSwi6A. Taken together, our results found two different transcripts generated from Swi6 , in which the alternative splice isoform of GlSwi6B participates in regulating the CWI of G . lucidum . This study provides the first insight into the alternative splicing isoform of GlSwi6B in the regulation of CWI signaling in fungi.

Microbial species performance responses to environmental changes: genomic traits and nutrient availability - Ang Hu; Minglei Ren; Jianjun Wang (Ecology, 2021)
How microbial species performance indicators, such as growth rate and carbon assimilation rate, respond to environmental changes is a challenging question, especially for complex communities. This limits our ability to understand how species performance responses to environmental changes (that is, species environmental responses) of microbes could be linked to genomic traits and nutrient availability. Based on stable isotope labeling of DNA, we propose a new approach with effect‐size metrics to quantify the species environmental responses of microbes by comparing the species performance between defined control and treatment groups. The species performance within microbial communities of the natural or altered environments could be quantitatively determined with quantitative stable isotope probing (qSIP). We further apply this approach, namely effect‐size qSIP, to measure species environmental responses upon carbon and nitrogen additions for soil bacteria on mountainsides and to understand their responses from the perspective of genomic traits. Towards high elevations, there is a stronger nitrogen limitation that is indicated by the higher aggregated responses, measured as community‐weighted means, of bacterial growth rate upon nitrogen additions. The aggregated responses are further explained by genomic traits, which show higher percentages of significant Kyoto Encyclopedia of Genes and Genomes (KEGG) orthologues (KOs) and more diverse KEGG pathways under nutrient additions including nitrogen, and further improve the explanatory power of microbial environmental responses. Nitrogen‐induced responses at the species level show the strongest associations with essential KOs for rare species, whereas carbon‐induced responses show the strongest associations for dominant species. We conclude that, in addition to environmental determinants such as nitrogen limitation, genomic traits are extremely important for predicting microbial environmental responses at both the community and species levels. Taking advantage of this new approach at the species level, we reveal that rare and dominant species differentially respond to nutrient enrichment via their metabolic traits. The approach and findings can lead to a more holistic understanding of microbial environmental responses in natural habitats, which will be essential for predicting microbial community responses to global environmental changes.

Regulation of glutamine synthetase activity by transcriptional and posttranslational modifications negatively influences ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Shuqi Song; Zehua Sun; Lingdan Lian; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Glutamine synthetase (GS), a central nitrogen metabolic enzyme, plays important roles in the nitrogen regulation network and secondary metabolism in fungi. However, the mechanisms by which external nitrogen sources regulate fungal GS activity have not been determined. Here, we found that GS activity was inhibited under nitrate conditions in Ganoderma lucidum . By constructing gs ‐silenced strains and adding 1 mM GS inhibitor to inhibit GS activity, we found that a decrease in GS activity led to a decrease in ganoderic acid biosynthesis. The transcription of gs increased approximately five fold under nitrate conditions compared with that under ammonia. Electrophoretic mobility shift and yeast one‐hybrid assay showed that gs was transcriptionally regulated by AreA. Although both gs expression and GS protein content increased under nitrate conditions, the GS activity still decreased. Treatment of recombinant GS with SIN‐1 (protein nitration donor) resulted in a strengthened nitration accompanied by a 71% decrease in recombinant GS activity. Furthermore, intracellular GS could be nitrated from mycelia cultivated under nitrate conditions. These results indicated that GS activity could be inhibited by NO‐mediated protein nitration. Our findings provide the first insight into the role of transcriptional and posttranslational regulation of GS activity in regulating secondary metabolism in fungi.

Nitric oxide regulates ganoderic acid biosynthesis by the S‐nitrosylation of aconitase under heat stress in Ganoderma lucidum - Rui Liu; Ting Zhu; Tao Yang; Zhengyan Yang; Ang Ren; Liang Shi; Jing Zhu; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2021)
Summary Nitric oxide (NO) is an important signalling molecule in stress response of organisms. We previously reported that NO decreases heat stress (HS)‐induced ganoderic acid (GA) accumulation in Ganoderma lucidum . To explore the mechanisms by which NO modulates GA biosynthesis under HS, the effect of NO on the reactive oxygen species (ROS) content was examined. The results showed that NO decreased the production of mitochondrial ROS (mitROS) by 60% under HS. Further research revealed that NO reduced the mitROS content by inhibiting aconitase (Acon) activity. The GA content in Acon‐silenced (Aconi) strains treated with NO donor did not differ significantly from that in untreated Aconi strains. To study the mechanism by which Acon activity is inhibited, the S‐nitrosylation level of Acon was determined. Biotin‐switch technology and mass spectrometry analysis were used to show that Acon is S‐nitrosylated at the Cys‐594 amino acid residue. Substitution of Cys‐594 with a Ser, which cannot be S‐nitrosylated, abolished the responsiveness of Acon to the NO‐induced reduction in its enzymatic activity. These findings demonstrate that NO inhibits Acon activity through S‐nitrosylation at Cys‐594. In summary, these findings describe mechanism by which NO regulates GA biosynthesis via S‐nitrosylation of Acon under HS condition in G . lucidum .

In Ganoderma lucidum , Glsnf1 regulates cellulose degradation by inhibiting GlCreA during the utilization of cellulose - Yanru Hu; Wenzhao Xu; Shishan Hu; Lingdan Lian; Jing Zhu; Liang Shi; Ang Ren; MingWen Zhao (Environmental Microbiology, 2020)
Summary Cellulose is a by‐product of agricultural production and an abundant waste. As a carbon source, cellulose can be degraded and utilized by fungi. Carbon sources, which act as nutrients, not only provide energy but also serve as regulators of gene expression, metabolism and growth, through various signalling networks that enable cells to sense and adapt to varying environmental conditions. Nutrient‐sensing pathways prioritize the use of preferred carbon sources and regulate the production of cellulose‐degrading enzymes when necessary. Understanding the regulation of the fungal cellulolytic response will become increasingly important because we strive to increase the efficiency of the utilization of these renewable energy sources. Here, we show that Glsnf1, a sucrose‐nonfermenting serine–threonine‐protein kinase 1 (Snf1)/AMP‐activated protein kinase homologue in medicinal macro basidiomycete Ganoderma lucidum , actively responds to carbon alterations and positively regulates cellulase activity and cellulase‐related gene transcription. The carbon catabolite repressor CreA, a zinc binuclear cluster transcription factor that mediates the sensing of nutrients and suppression of the transcription of a number of genes necessary for the consumption of a less preferred carbon source, participates in the Glsnf1‐mediated regulation of cellulases. Glsnf1 not only negatively regulates the transcription level of the CreA gene but also hinders its localization in the nucleus. Overall, our findings reveal a key nutrient‐sensing mechanism that is critical for the modulation of carbon source adaptation in G . lucidum .

Dual functions of AreA, a GATA transcription factor, on influencing ganoderic acid biosynthesis in Ganoderma lucidum - Jing Zhu; Zehua Sun; Dengke Shi; Shuqi Song; Lingdan Lian; Liang Shi; Ang Ren; Hanshou Yu; Mingwen Zhao (Environmental Microbiology, 2019)
Summary Nitrogen metabolism repression (NMR) has been well studied in filamentous fungi, but the molecular mechanism of its effects on fungal secondary metabolism has been generally unexplored. Ganoderic acid (GA) biosynthesis in Ganoderma lucidum differs between ammonia and nitrate nitrogen sources. To explain the functions of NMR in secondary metabolism, AreA, which is a core transcription factor of NMR, was characterized in G . lucidum . The transcription level of AreA was dramatically increased (approximately 4.5‐folds), with the nitrate as the sole nitrogen source, compared with that with ammonia as the source. In addition, the expression of related genes involved in NMR was changed (upregulated of MeaB and downregulated of Nmr and GlnA ) when AreA was knockdown. Yeast one‐hybrid and electrophoretic mobility shift assay results showed that AreA could directly bind to the promoter of fps (encoding farnesyl‐diphosphate synthase) to activate its expression. However, GA biosynthesis was increased (27% in the ammonia source and 77% in the nitrate source) in AreAi mutant strains versus that in control strains. These results showed that another important factor must participate in regulating GA biosynthesis other than the direct activation of AreA. Furthermore, we found that the content of nitric oxide (NO) was increased approximately 2.7‐folds in the nitrate source compared with that in the ammonia. By adding the NO donor (SNP) or scavenger (cPTIO) and using NR ‐silenced or NR ‐overexpressed strains, we found that there was a negative correlation between the NO contents and GA biosynthesis. NO generated by nitrate reductase (NR) during the nitrogen utilization burst and could negatively influence GA biosynthesis. As a global transcription factor, AreA could also regulate the expression of NR . Our studies provide novel insight into the dual functions of AreA in GA biosynthesis during nitrogen assimilation.

Regression based overall survival prediction of glioblastoma multiforme patients using a single discovery cohort of multi-institutional multi-channel MR images - Parita Sanghani; Beng Ti Ang; Nicolas Kon Kam King; Hongliang Ren (Medical & Biological Engineering & Computing, 2019)

14-3-3 Proteins: a window for a deeper understanding of fungal metabolism and development - Liang Shi; Ang Ren; Jing Zhu; Hanshou Yu; Ailiang Jiang; Huihua Zheng; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2019)

Conversion of phosphatidylinositol (PI) to PI4‐phosphate (PI4P) and then to PI(4,5)P 2 is essential for the cytosolic Ca 2+ concentration under heat stress in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2018)
Summary How cells drive the phospholipid signal response to heat stress (HS) to maintain cellular homeostasis is a fundamental issue in biology, but the regulatory mechanism of this fundamental process is unclear. Previous quantitative analyses of lipids showed that phosphatidylinositol (PI) accumulates after HS in Ganoderma lucidum , implying the inositol phospholipid signal may be associated with HS signal transduction. Here, we found that the PI‐4‐kinase and PI‐4‐phosphate‐5‐kinase activities are activated and that their lipid products PI‐4‐phosphate and PI‐4,5‐bisphosphate are increased under HS. Further experimental results showed that the cytosolic Ca 2+ ([Ca 2+ ] c ) and ganoderic acid (GA) contents induced by HS were decreased when cells were pretreated with Li + , an inhibitor of inositol monophosphatase, and this decrease could be rescued by PI and PI‐4‐phosphate. Furthermore, inhibition of PI‐4‐kinases resulted in a decrease in the Ca 2+ and GA contents under HS that could be rescued by PI‐4‐phosphate but not PI. However, the decrease in the Ca 2+ and GA contents by silencing of PI‐4‐phosphate‐5‐kinase could not be rescued by PI‐4‐phosphate. Taken together, our study reveals the essential role of the step converting PI to PI‐4‐phosphate and then to PI‐4,5‐bisphosphate in [Ca 2+ ] c signalling and GA biosynthesis under HS.

Erratum to: Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Phospholipase D and phosphatidic acid mediate heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Dai Chen; Ya‐Ping Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Phospholipid‐mediated signal transduction plays a key role in responses to environmental changes, but little is known about the role of phospholipid signalling in microorganisms. Heat stress (HS) is one of the most important environmental factors. Our previous study found that HS could induce the biosynthesis of the secondary metabolites, ganoderic acids (GA). Here, we performed a comprehensive mass spectrometry‐based analysis to investigate HS‐induced lipid remodelling in Ganoderma lucidum . In particular, we observed a significant accumulation of phosphatidic acid (PA) on HS. Further genetic tests in which pld ‐silencing strains were constructed demonstrated that the accumulation of PA is dependent on HS‐activated phospholipase D (PLD) hydrolysing phosphatidylethanolamine. Furthermore, we determined the role of PLD and PA in HS‐induced secondary metabolism in G . lucidum . Exogenous 1‐butanol, which decreased PLD‐mediated formation of PA, reverses the increased GA biosynthesis that was elicited by HS. The pld ‐silenced strains partly blocked HS‐induced GA biosynthesis, and this block can be reversed by adding PA. Taken together, our results suggest that PLD and PA are involved in the regulation of HS‐induced secondary metabolism in G . lucidum . Our findings provide key insights into how microorganisms respond to heat stress and then consequently accumulate secondary metabolites by phospholipid remodelling.

Membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Tian‐Jun Zhang; Xiao‐Xiao Lu; Bao‐Liang Ma; Ang Ren; Liang Shi; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum has become a potential model system for evaluating how environmental factors regulate the secondary metabolism of basidiomycetes. Heat stress (HS) is one of the most important environmental factors. It was previously reported that HS could induce the biosynthesis of ganoderic acids (GA). In this study, we found that HS increased GA biosynthesis and also significantly increased cell membrane fluidity. Furthermore, our results showed that addition of the membrane rigidifier dimethylsulfoxide (DMSO) could revert the increased GA biosynthesis elicited by HS. These results indicate that an increase in membrane fluidity is associated with HS‐induced GA biosynthesis. Further evidence showed that the GA content was decreased in D9des ‐silenced strains and could be reverted to WT levels by addition of the membrane fluidizer benzyl alcohol (BA). In contrast, GA content was increased in D9des ‐overexpression strains and could be reverted to WT levels by the addition of DMSO. Furthermore, both membrane fluidity and GA biosynthesis induced by HS could be reverted by DMSO in WT and D9des ‐silenced strains. To the best of our knowledge, this is the first report demonstrating that membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in filamentous fungi.

Ethylene promotes mycelial growth and ganoderic acid biosynthesis in Ganoderma lucidum - Guang Zhang; Ang Ren; Fengli Wu; Hanshou Yu; Liang Shi; Mingwen Zhao (Biotechnology Letters, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Association Between a Variant in ADAMTS5 and the Susceptibility to Hepatocellular Carcinoma in a Chinese Han Population - Chongyi Li; Yanli Xiong; Zhaoyang Zhong; Shiheng Zhang; Yu Peng; Lin’ang Wang; Nan Dai; Mengxia Li; Tao Ren; Lixia Gan; Dong Wang (Cell Biochemistry and Biophysics, 2015)

The bacterial lipopeptide iturins induce V erticillium dahliae cell death by affecting fungal signalling pathways and mediate plant defence responses involved in pathogen‐associated molecular pattern‐triggered immunity - Qin Han; Fengli Wu; Xiaonan Wang; Hong Qi; Liang Shi; Ang Ren; Qinghai Liu; Mingwen Zhao; Canming Tang (Environmental Microbiology, 2015)
Summary V erticillium wilt in cotton caused by V erticillium dahliae is one of the most serious plant diseases worldwide. Because no known fungicides or cotton cultivars provide sufficient protection against this pathogen, V . dahliae causes major crop yield losses. Here, an isolated cotton endophytic bacterium, designated B acillus amyloliquefaciens 41 B ‐1, exhibited greater than 50% biocontrol efficacy against V . dahliae in cotton plants under greenhouse conditions. Through high‐performance liquid chromatography and mass analysis of the filtrate, we found that the antifungal compounds present in the strain 41 B ‐1 culture filtrate were a series of isoforms of iturins. The purified iturins suppressed V . dahliae microsclerotial germination in the absence or presence of cotton. Treatment with the iturins induced reactive oxygen species bursts, H og1 mitogen‐activated protein kinase (MAPK) activation and defects in cell wall integrity. The oxidative stress response and high‐osmolarity glycerol pathway contribute to iturins resistance in V . dahliae . In contrast, the S lt2 MAPK pathway may be involved in iturins sensitivity in this fungus. In addition to antagonism, iturins could induce plant defence responses as activators and mediate pathogen‐associated molecular pattern‐triggered immunity. These findings suggest that iturins may affect fungal signalling pathways and mediate plant defence responses against V . dahliae .

Transcript and metabolite alterations increase ganoderic acid content in Ganoderma lucidum using acetic acid as an inducer - Ang Ren; Xiong-Biao Li; Zhi-Gang Miao; Liang Shi; Ai-Liang Jaing; Ming-Wen Zhao (Biotechnology Letters, 2014)

Functions of the nicotinamide adenine dinucleotide phosphate oxidase family in G anoderma lucidum : an essential role in ganoderic acid biosynthesis regulation, hyphal branching, fruiting body development, and oxidative‐stress resistance - Dashuai Mu; Chenyang Li; Xuchen Zhang; Xiongbiao Li; Liang Shi; Ang Ren; Mingwen Zhao (Environmental Microbiology, 2014)
Summary G anoderma lucidum has drawn worldwide interest with regard to its secondary metabolism and pharmaceutical activity. However, the development of such research has been limited because of a lack of basic biological knowledge. Nicotinamide adenine dinucleotide phosphate oxidases (Nox) have recently been highlighted because of the many important biological roles in plants and animals; however, the exact functions of Nox are still not fully understood in fungi. In this study, we identified two N ox isoforms ( NoxA and NoxB ) and a regulator, NoxR . RNA interference was used, and silencing of the Nox isoforms and NoxR expression indicated a central role for these genes in hyphal branching, fruiting body development, reactive oxygen species ( ROS ) generation, ROS resistance and ganoderic acid biosynthesis regulation. Further mechanistic investigation revealed that N ox‐generated ROS elevated cytosolic Ca 2+ levels by activating a plasma membrane Ca 2+ influx pathway, thereby inducing the Ca 2+ signal pathway to regulate ganoderic acid biosynthesis and hyphal branching. Importantly, our results highlight the N ox functions in signal crosstalk between ROS and Ca 2+ , and these findings provide an excellent opportunity to identify the potential pathway linking ROS networks to calcium signalling in fungi and suggest that plants, animals and fungi share a conserved signal‐crosstalk mechanism.

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

Microbial community analysis of three municipal wastewater treatment plants in winter and spring using culture-dependent and culture-independent methods - Di Cui; Ang Li; Si Zhang; Changlong Pang; Jixian Yang; Jingbo Guo; Fang Ma; Jihua Wang; Nanqi Ren (World Journal of Microbiology and Biotechnology, 2012)

Molecular cloning, characterization, and function analysis of a mevalonate pyrophosphate decarboxylase gene from Ganoderma lucidum - Liang Shi; Lei Qin; Yingjie Xu; Ang Ren; Xing Fang; Dashuai Mu; Qi Tan; Mingwen Zhao (Molecular Biology Reports, 2012)

Development of a simple and efficient transformation system for the basidiomycetous medicinal fungus Ganoderma lucidum - Liang Shi; Xing Fang; Mengjiao Li; Dashuai Mu; Ang Ren; Qi Tan; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2012)